Preparation of Bi2O3/TiO2–Montmorillonite Nanocomposites and Their Applications to the Photodegradation of Pentachlorophenol - Nacéra Boumahdi; Amel Hadj-Ziane-Zafour; Hafsa Yaiche-Achour; Hussein Khalaf (Bulletin of Chemical Reaction Engineering & Catalysis, 2022)
In the past decades, there has been a growing tendency to study the different techniques that can increase the photocatalytic efficiency as well as recyclability of new products “photocatalysts” for water treatment. In this last research the effect of bismuth addition to titanium was investigated. Bi/Ti-pillared montmorillonites have been prepared from natural Algerian bentonite exactly from deposits of Maghnia situated in the west side of the country. These nanocomposites were characterized by X-ray diffraction (XRD), Brunauer-Emmet-Teller (BET), scanning electron microscopy (SEM) methods, and Fourier Transformed Infrared (FT-IR). The photocatalytic activities have been tested for the removal of pentaclorophenol (PCP) in water. The effect of preparation conditions, the pH of the solution and photocatalysts concentration, on these activities has been investigated. It was found that the photocatalytic degradation increase by addition of bismuth in pillaring process. The Mont-Bi-Ti is shown to be the best photocatalyst in term of photocatalytic activity. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).